Transparent heat-conducting adhesive, preparation method thereof and heat-conducting adhesive tape
By using transparent quartz powder and nanothermal conducting powder in transparent thermal conducting materials with high refractive index adhesives, the balance problem between thermal conductivity and light transmittance of existing materials is solved, and efficient thermal conductivity and high light transmittance effects are achieved.
Patent Information
- Application Number
- CN202411939678.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-11
AI Technical Summary
The existing transparent thermal conductivity materials are difficult to maintain high light transmittance while improving the thermal conductivity, and the poor dispersion and sharp increase in viscosity of nanomaterials affect construction properties.
Transparent and high thermal conductivity transparent quartz powder material is used, and the Z-direction thermal conductivity path is formed by reasonably designing its size and addition amount. It is matched with nano-thermal conduction powder to form a stable thermal conductivity path. At the same time, high refractive index adhesive material is selected to improve the light transmittance of the material.
The balance of high thermal conductivity and high light transmittance is achieved, which reduces haze and improves the overall performance of the material, and is suitable for applications such as display devices and modules.
Smart Images

Figure BDA0005212313990000141
Abstract
Description
Technical Field
[0001] The invention relates to the field of thermally conductive adhesive materials, and in particular to a transparent thermally conductive adhesive, a preparation method thereof and a thermally conductive adhesive tape. Background Art
[0002] With the development of electronic product technology, the packaging density of components is constantly increasing. The heat dissipation problem has become a bottleneck problem that limits the increase in packaging density. The existing thermal conductive materials are generally made of ceramic powders, metal particles or carbon materials as thermal conductive fillers and composite polymer materials. However, since the above particles are all colored and the amount added is relatively high, the light transmittance of the thermal conductive materials is very poor. This requires not only that the materials have good thermal conductivity for display devices and modules, but also that the materials do not affect their light transmittance. For transparent thermal conductive materials, the existing technology generally uses nano thermal conductive particles, nano fibers and other materials that are smaller than the wavelength of visible light. These nano materials themselves have a small particle size and a low addition amount, which cannot form a thermal conductive path to achieve a higher thermal conductivity effect. In addition, these nano materials themselves have a large specific surface area and are difficult to disperse in inorganic materials. At the same time, the viscosity of the system will rise sharply, affecting the construction performance. Or use materials such as glass powder and transparent powder, but the thermal conductivity of these materials is still low and cannot achieve a good thermal conductivity effect.
[0003] Therefore, it is necessary to improve the existing technology to provide a more reliable solution. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a transparent thermally conductive adhesive, a preparation method thereof and a thermally conductive tape in view of the deficiencies in the above-mentioned prior art.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: in the first aspect of the present invention, a transparent thermally conductive adhesive is provided, comprising the following raw material components in parts by weight: 100 parts of transparent adhesive, 75-150 parts of transparent thermally conductive filler, 1-20 parts of nano thermally conductive filler, 1-3 parts of surface modification additive, and 150-300 parts of a first solvent.
[0006] Preferably, the transparent adhesive is any one of transparent acrylic, transparent polyurethane, transparent epoxy, and transparent silicone adhesive, and the refractive index of the transparent adhesive is 1.5-1.6.
[0007] Preferably, the transparent adhesive is a transparent acrylic adhesive added with a curing agent, and the raw materials for preparing the transparent acrylic adhesive include, by weight: 15-40 parts of high refractive index acrylic monomer, 2-20 parts of hard monomer, 40-70 parts of soft monomer, 1-5 parts of functional monomer, 0.1-1 parts of initiator and 60-150 parts of second solvent;
[0008] The amount of curing agent added is 1-4 parts.
[0009] Preferably, the method for preparing the transparent adhesive comprises the following steps:
[0010] 1) Preparation of transparent acrylic adhesive:
[0011] By weight, 15-40 parts of a high refractive index acrylic monomer, 2-20 parts of a hard monomer, 40-70 parts of a soft monomer, 1-5 parts of a functional monomer, 0.1-1 parts of an initiator and 60-150 parts of a second solvent are mixed, and reacted under nitrogen flow to obtain a transparent acrylic adhesive;
[0012] 2) Add 1-4 parts by weight of a curing agent to the transparent acrylic adhesive and stir evenly to obtain the transparent adhesive.
[0013] Preferably, the high refractive index acrylic monomer is at least one of o-phenylphenoxyethyl acrylate, 4-biphenylmethanol acrylate, benzyl methacrylate, 1-naphthyl methacrylate, trimethylolpropane tris(3-mercaptopropionate) and the like.
[0014] The soft monomer is at least one of hydroxyethyl acrylate and cyclohexyl acrylate;
[0015] The hard monomer is isobornyl acrylate;
[0016] The functional monomer is at least one of hydroxyethyl acrylate and acrylic acid;
[0017] The curing agent is one or more of an epoxy curing agent, an isocyanate curing agent, and an aziridine curing agent;
[0018] The first solvent and the second solvent are one or more of ethyl acetate, butanone, acetone, toluene, xylene, and butyl acetate.
[0019] Preferably, the transparent thermally conductive filler is transparent quartz powder, with a thermal conductivity of 7-10 W / m·K and a refractive index of 1.54-1.55;
[0020] The particle size of the transparent quartz powder and the thickness of the adhesive layer formed after the transparent thermal conductive adhesive is cured satisfy the following relationship: D50 particle size>1 / 2 adhesive thickness, D90 particle size<3 / 4 adhesive thickness, and D100 particle size<adhesive thickness.
[0021] Preferably, the nano thermal conductive filler is one or more of nano aluminum oxide, nano boron nitride, nano titanium oxide, nano zinc oxide, nano aluminum nitride, nano diamond, etc., and the maximum particle size of the nano filler is less than 380 nm.
[0022] Preferably, the surface modification aid is one or more of a coupling agent, a surfactant, and a dispersant.
[0023] A second aspect of the present invention provides a method for preparing the transparent thermally conductive adhesive as described above, comprising the following steps:
[0024] S1, dividing the first solvent into two parts, mixing the nano thermal conductive filler, the surface modification agent, and the first part of the first solvent and soaking them for 12-48 hours, and then dispersing them for 10-60 minutes to obtain a nano thermal conductive filler slurry;
[0025] S2, adding a transparent thermally conductive filler into the second part of the first solvent and soaking for 10-40 minutes, then adding a transparent adhesive, stirring for 10-30 minutes, and then adding the nano thermally conductive filler slurry obtained in step S1, and continuing to disperse for 10-60 minutes to obtain the transparent thermally conductive adhesive.
[0026] The third aspect of the present invention provides a transparent thermally conductive tape, which is prepared by the following method: the transparent thermally conductive adhesive as described above is evenly coated on the surface of the release material, baked at 60-130°C for 5-10 minutes, and matured at 35-70°C for 1-5 days to obtain the transparent thermally conductive tape.
[0027] The beneficial effects of the present invention are:
[0028] The present invention provides a transparent thermally conductive adhesive, a preparation method thereof and a thermally conductive tape. The present invention adopts a transparent quartz powder material with a high thermal conductivity, and reasonably designs its size and addition amount to directly form a thermal conduction path in the Z direction, and forms a stable thermal conduction path by matching with a nano thermally conductive powder to achieve a higher thermal conductivity; simultaneously, an adhesive material with a high refractive index is selected to match with it, which can reduce the refraction of light in the material, improve the overall light transmittance of the material, and reduce the haze; the product of the present invention has a good market application prospect. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0030] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0031] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0032] The invention provides a transparent thermally conductive adhesive, comprising the following raw material components in parts by weight: 100 parts of a transparent adhesive, 75-150 parts of a transparent thermally conductive filler, 1-20 parts of a nano thermally conductive filler, 1-3 parts of a surface modification auxiliary agent, and 150-300 parts of a first solvent.
[0033] In a preferred embodiment, the transparent adhesive is any one of transparent acrylic, transparent polyurethane, transparent epoxy, and transparent silicone adhesive, and the refractive index of the transparent adhesive is 1.5-1.6. More preferably, the transparent adhesive is a transparent acrylic adhesive with a refractive index of about 1.5-1.6.
[0034] In a preferred embodiment, the transparent adhesive is a transparent acrylic adhesive added with a curing agent, and the raw materials for preparing the transparent acrylic adhesive include, by weight: 15-40 parts of a high refractive index acrylic monomer, 2-20 parts of a hard monomer, 40-70 parts of a soft monomer, 1-5 parts of a functional monomer, 0.1-1 parts of an initiator, and 60-150 parts of a second solvent;
[0035] The amount of curing agent added is 1-4 parts.
[0036] In a preferred embodiment, the method for preparing the transparent adhesive comprises the following steps:
[0037] 1) Preparation of transparent acrylic adhesive:
[0038] By weight, 15-40 parts of a high refractive index acrylic monomer, 2-20 parts of a hard monomer, 40-70 parts of a soft monomer, 1-5 parts of a functional monomer, 0.1-1 parts of an initiator and 60-150 parts of a second solvent are mixed, and reacted under nitrogen flow to obtain a transparent acrylic adhesive;
[0039] 2) Add 1-4 parts by weight of a curing agent to the transparent acrylic adhesive and stir evenly to obtain a transparent adhesive.
[0040] In a preferred embodiment, the high refractive index acrylic monomer is at least one of o-phenylphenoxyethyl acrylate, 4-biphenylmethanol acrylate, benzyl methacrylate, 1-naphthyl methacrylate, trimethylolpropane tris(3-mercaptopropionate) and the like.
[0041] In a preferred embodiment, the soft monomer is at least one of hydroxyethyl acrylate and cyclohexyl acrylate.
[0042] In a preferred embodiment, the hard monomer is isobornyl acrylate.
[0043] In a preferred embodiment, the functional monomer is at least one of hydroxyethyl acrylate and acrylic acid.
[0044] In a preferred embodiment, the curing agent is one or more of an epoxy curing agent, an isocyanate curing agent, and an aziridine curing agent.
[0045] In a preferred embodiment, the first solvent and the second solvent are one or more of ethyl acetate, butanone, acetone, toluene, xylene, and butyl acetate.
[0046] In a preferred embodiment, the transparent thermally conductive filler is transparent quartz powder, with a thermal conductivity of 7-10 W / m·K and a refractive index of 1.54-1.55. The whiteness of the transparent quartz powder is >95%, and it has high transparency. It has the characteristics of high purity, low ion content, low conductivity, and excellent electrical insulation. At the same time, its sphericity rate is >95%, and the particle size distribution is stable and concentrated. The more preferred particle size of the thermally conductive filler is D50>1 / 2 of the glue thickness, D90<3 / 4 of the glue thickness, and D100<the glue thickness.
[0047] In a preferred embodiment, the nano thermal conductive filler is one or more of nano aluminum oxide, nano boron nitride, nano titanium oxide, nano zinc oxide, nano aluminum nitride, nano diamond, etc., and the maximum particle size of the nano filler is less than 380 nm.
[0048] In a preferred embodiment, the surface modification aid is one or more of a coupling agent, a surfactant, and a dispersant, which is used to perform surface modification on the nano thermal conductive filler to achieve a better dispersion effect.
[0049] The present invention also provides a method for preparing the transparent thermally conductive adhesive as above, comprising the following steps:
[0050] S1. Divide the first solvent into two parts, mix and soak the nano thermal conductive filler, the surface modification agent, and the first part of the first solvent for 12-48 hours, and then use a sand mill, a high-speed disperser, a ball mill, a planetary ball mill and other equipment to disperse at high speed for 10-60 minutes to obtain a nano thermal conductive filler slurry;
[0051] S2, adding the transparent thermally conductive filler into the second part of the first solvent and soaking for 10-40 minutes, then adding the transparent adhesive, stirring for 10-30 minutes, and then adding the nano thermally conductive filler slurry obtained in step S1, and continuing to disperse for 10-60 minutes to obtain a transparent thermally conductive adhesive.
[0052] The present invention also provides a transparent thermally conductive tape, which is prepared by the following method: the transparent thermally conductive adhesive as claimed in claim 9 is evenly coated on the surface of the release material by a coating method such as a scraper or slit extrusion, dried at 60-130° C., and aged at 35-70° C. for 1-5 days to obtain a transparent thermally conductive tape.
[0053] The release material can be one or more of PET release film, PE release film, release paper, etc.
[0054] The transparent thermal conductive adhesive can also be coated on a transparent substrate to form a single-sided or double-sided thermal conductive material. The transparent substrate can be made of transparent PET, PC, BOPP, CPI and other materials.
[0055] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.
[0056] Example 1
[0057] A transparent thermally conductive adhesive, the raw material ratio of which is:
[0058] In parts by weight, the transparent adhesive, the transparent thermal conductive filler, the nano thermal conductive filler, the surface modification additive, and the ethyl acetate are 100 parts, 118 parts, 15 parts, 0.3 parts, and 150 parts, respectively.
[0059] The preparation method of the transparent adhesive comprises the following steps:
[0060] 1) Preparation of transparent acrylic adhesive:
[0061] By weight, 20 parts of o-phenylphenoxyethyl acrylate, 16 parts of 4-biphenylmethanol acrylate, 15 parts of hydroxyethyl acrylate as a soft monomer, 30 parts of cyclohexyl acrylate, 15 parts of isobornyl acrylate as a hard monomer, 3 parts of hydroxyethyl acrylate as a functional monomer, 1 part of acrylic acid, 0.6 parts of azobisisobutyronitrile initiator, 80 parts of ethyl acetate, and 40 parts of butanone are mixed, and reacted at 66° C. for 3 hours, 75° C. for 2 hours, and 78° C. for 2 hours under nitrogen flow to obtain a transparent acrylic adhesive; the refractive index is 1.54, and the transmittance is 95%;
[0062] 2) Add 2 parts by weight of curing agent isocyanate L75 to the transparent acrylic adhesive and stir evenly to obtain a transparent adhesive.
[0063] The transparent thermal conductive filler is a spherical quartz powder with a D50 of 30μm and a D100 of 46μm, the nano thermal conductive filler is a spherical nano alumina powder with a D50 of 28nm and a D100 of 265nm, and the surface dispersant is the acrylate hyperdispersant DISPERBYK-2022 purchased from German BYK. The cross-sectional area ratio of the transparent thermal conductive filler to the transparent adhesive is about 2:3, which is the ratio of the cross-sectional area of the transparent thermal conductive filler to the transparent adhesive after the adhesive is coated and formed into a film.
[0064] The preparation method of the transparent thermally conductive adhesive comprises the following steps:
[0065] S1, mixing a nano thermally conductive filler, a surface modification agent, and 45 parts of ethyl acetate and soaking them for 24 hours, and then dispersing them in a ball mill at 2000 rpm for 20 minutes to obtain a nano thermally conductive filler slurry;
[0066] S2. Add a transparent thermally conductive filler to 60 parts of ethyl acetate and soak for 20 minutes, then add a transparent adhesive, and then use a high-speed disperser to stir for 30 minutes at 1000 rpm, then add the nano thermally conductive filler slurry obtained in step S1 and rinse the dispersed thermally conductive filler with the remaining 45 parts of ethyl acetate to ensure that the filler in S1 is completely added, and continue to disperse for 30 minutes at 1000 rpm using a high-speed disperser to obtain a transparent thermally conductive adhesive.
[0067] Example 2
[0068] A transparent thermally conductive adhesive, the raw material ratio of which is:
[0069] In parts by weight, the transparent adhesive, the transparent thermal conductive filler, the nano thermal conductive filler, the surface modification additive, and the ethyl acetate are 100 parts, 118 parts, 10 parts, 0.2 parts, and 150 parts, respectively.
[0070] The preparation method of the transparent adhesive comprises the following steps:
[0071] 1) Preparation of transparent acrylic adhesive:
[0072] By weight, 20 parts of o-phenylphenoxyethyl acrylate, 16 parts of 4-biphenylmethanol acrylate, 15 parts of hydroxyethyl acrylate as a soft monomer, 30 parts of cyclohexyl acrylate, 15 parts of isobornyl acrylate as a hard monomer, 3 parts of hydroxyethyl acrylate as a functional monomer, 1 part of acrylic acid, 0.6 parts of azobisisobutyronitrile initiator, 80 parts of ethyl acetate, and 40 parts of butanone are mixed, and reacted at 66° C. for 3 hours, 75° C. for 2 hours, and 78° C. for 2 hours under nitrogen flow to obtain a transparent acrylic adhesive; the refractive index is 1.54, and the transmittance is 95%;
[0073] 2) Add 2 parts by weight of curing agent isocyanate L75 to the transparent acrylic adhesive and stir evenly to obtain a transparent adhesive.
[0074] The transparent thermal conductive filler is a spherical quartz powder with a D50 of 30μm and a D100 of 46μm, the nano thermal conductive filler is a spherical boron nitride powder with a D50 of 35nm and a D100 of 260nm, and the surface dispersant is an acrylate hyperdispersant DISPERBYK-2022 purchased from BYK, Germany. The cross-sectional area ratio of the transparent thermal conductive filler to the transparent adhesive is about 3:2, which is the ratio of the cross-sectional area of the transparent thermal conductive filler to the transparent adhesive after the adhesive is coated and formed into a film.
[0075] The preparation method of the transparent thermally conductive adhesive comprises the following steps:
[0076] S1, mixing a nano thermally conductive filler, a surface modification agent, and 30 parts of ethyl acetate and soaking them for 24 hours, and then dispersing them in a ball mill at 2000 rpm for 20 minutes to obtain a nano thermally conductive filler slurry;
[0077] S2. Add a transparent thermally conductive filler to 60 parts of ethyl acetate and soak for 20 minutes, then add a transparent adhesive, use a high-speed disperser to stir at 1000 rpm for 30 minutes, then add the nano thermally conductive filler slurry obtained in step S1 and rinse the dispersed thermally conductive filler with the remaining 60 parts of ethyl acetate to ensure that the filler in S1 is completely added, and continue to disperse for 30 minutes at 1000 rpm using a high-speed disperser to obtain a transparent thermally conductive adhesive.
[0078] Example 3
[0079] A transparent thermally conductive adhesive, the raw material ratio of which is:
[0080] In parts by weight, the transparent adhesive, the transparent thermal conductive filler, the nano thermal conductive filler, the surface modification additive, and the ethyl acetate are 100 parts, 78 parts, 15 parts, 0.3 parts, and 150 parts, respectively.
[0081] The preparation method of the transparent adhesive comprises the following steps:
[0082] 1) Preparation of transparent acrylic adhesive:
[0083] By weight, 20 parts of o-phenylphenoxyethyl acrylate, 16 parts of 4-biphenylmethanol acrylate, 15 parts of hydroxyethyl acrylate as a soft monomer, 30 parts of cyclohexyl acrylate, 15 parts of isobornyl acrylate as a hard monomer, 3 parts of hydroxyethyl acrylate as a functional monomer, 1 part of acrylic acid, 0.6 parts of azobisisobutyronitrile initiator, 80 parts of ethyl acetate, and 40 parts of butanone are mixed, and reacted at 66° C. for 3 hours, 75° C. for 2 hours, and 78° C. for 2 hours under nitrogen flow to obtain a transparent acrylic adhesive; the refractive index is 1.54, and the transmittance is 95%;
[0084] 2) Add 2 parts by weight of curing agent isocyanate L75 to the transparent acrylic adhesive and stir evenly to obtain a transparent adhesive.
[0085] The transparent thermal conductive filler is spherical quartz powder with a D50 of 30μm and a D100 of 46μm, the nano thermal conductive filler is spherical diamond powder with a D50 of 25nm and a D100 of 260nm, and the surface dispersant is the acrylate hyperdispersant DISPERBYK-2022 purchased from BYK, Germany. The cross-sectional area ratio of the transparent thermal conductive filler to the transparent adhesive is about 1:1, which is the ratio of the cross-sectional area of the transparent thermal conductive filler to the transparent adhesive after the adhesive is coated and formed into a film.
[0086] The preparation method of the transparent thermally conductive adhesive comprises the following steps:
[0087] S1, mixing a nano thermally conductive filler, a surface modification agent, and 50 parts of ethyl acetate and soaking them for 24 hours, and then dispersing them in a ball mill at 2000 rpm for 20 minutes to obtain a nano thermally conductive filler slurry;
[0088] S2. Add a transparent thermally conductive filler to 40 parts of ethyl acetate and soak for 20 minutes, then add a transparent adhesive, use a high-speed disperser to stir at 1000 rpm for 30 minutes, then add the nano thermally conductive filler slurry obtained in step S1 and use the remaining 60 parts of ethyl acetate to rinse the dispersed thermally conductive filler to ensure that the filler in S1 is completely added, and use a high-speed disperser to continue dispersing for 30 minutes at 1000 rpm to obtain a transparent thermally conductive adhesive.
[0089] Example 4
[0090] A transparent thermally conductive adhesive, the raw material ratio of which is:
[0091] In parts by weight, the transparent adhesive, the transparent thermal conductive filler, the nano thermal conductive filler, the surface modification additive, and the ethyl acetate are 100 parts, 118 parts, 2 parts, 0.2 parts, and 150 parts, respectively.
[0092] The preparation method of the transparent adhesive comprises the following steps:
[0093] 1) Preparation of transparent acrylic adhesive:
[0094] By weight, 20 parts of o-phenylphenoxyethyl acrylate, 16 parts of 4-biphenylmethanol acrylate, 15 parts of hydroxyethyl acrylate as a soft monomer, 30 parts of cyclohexyl acrylate, 15 parts of isobornyl acrylate as a hard monomer, 3 parts of hydroxyethyl acrylate as a functional monomer, 1 part of acrylic acid, 0.6 parts of azobisisobutyronitrile initiator, 80 parts of ethyl acetate, and 40 parts of butanone are mixed, and reacted at 66° C. for 3 hours, 75° C. for 2 hours, and 78° C. for 2 hours under nitrogen flow to obtain a transparent acrylic adhesive; the refractive index is 1.54, and the transmittance is 95%;
[0095] 2) Add 2 parts by weight of curing agent isocyanate L75 to the transparent acrylic adhesive and stir evenly to obtain a transparent adhesive.
[0096] The transparent thermal conductive filler is spherical quartz powder with a D50 of 30μm and a D100 of 46μm, the nano thermal conductive filler is boron nitride nanotube powder with an average diameter of 50nm and a length of 5-10μm, and the surface dispersant is the acrylate hyperdispersant DISPERBYK-2022 purchased from BYK, Germany. The cross-sectional area ratio of the transparent thermal conductive filler to the transparent adhesive is about 3:2, which is the ratio of the cross-sectional area of the transparent thermal conductive filler to the transparent adhesive after the adhesive is coated and formed into a film.
[0097] The preparation method of the transparent thermally conductive adhesive comprises the following steps:
[0098] S1, mixing a nano thermally conductive filler, a surface modification agent, and 30 parts of ethyl acetate and soaking them for 24 hours, and then dispersing them in a ball mill at 2000 rpm for 20 minutes to obtain a nano thermally conductive filler slurry;
[0099] S2. Add a transparent thermally conductive filler to 60 parts of ethyl acetate and soak for 20 minutes, then add a transparent adhesive, use a high-speed disperser to stir at 1000 rpm for 30 minutes, then add the nano thermally conductive filler slurry obtained in step S1 and use the remaining 60 parts of ethyl acetate to rinse the dispersed thermally conductive filler to ensure that the filler in S1 is completely added, and use a high-speed disperser to continue dispersing for 30 minutes at 1000 rpm to obtain a transparent thermally conductive adhesive.
[0100] Example 5
[0101] A transparent thermally conductive adhesive, the raw material ratio of which is:
[0102] In parts by weight, the transparent adhesive, the transparent thermal conductive filler, the nano thermal conductive filler, the surface modification additive, and the ethyl acetate are 100 parts, 145 parts, 15 parts, 0.3 parts, and 150 parts, respectively.
[0103] The preparation method of the transparent adhesive comprises the following steps:
[0104] 1) Preparation of transparent acrylic adhesive:
[0105] By weight, 20 parts of o-phenylphenoxyethyl acrylate, 16 parts of 4-biphenylmethanol acrylate, 15 parts of hydroxyethyl acrylate as a soft monomer, 30 parts of cyclohexyl acrylate, 15 parts of isobornyl acrylate as a hard monomer, 3 parts of hydroxyethyl acrylate as a functional monomer, 1 part of acrylic acid, 0.6 parts of azobisisobutyronitrile initiator, 80 parts of ethyl acetate, and 40 parts of butanone are mixed, and reacted at 66° C. for 3 hours, 75° C. for 2 hours, and 78° C. for 2 hours under nitrogen flow to obtain a transparent acrylic adhesive; the refractive index is 1.54, and the transmittance is 95%;
[0106] 2) Add 2 parts by weight of curing agent isocyanate L75 to the transparent acrylic adhesive and stir evenly to obtain a transparent adhesive.
[0107] The transparent thermal conductive filler is spherical quartz powder with a D50 of 30μm and a D100 of 46μm, the nano thermal conductive filler is spherical alumina powder with a D50 of 28nm and a D100 of 265nm, and the surface dispersant is the acrylate hyperdispersant DISPERBYK-2022 purchased from BYK, Germany. The cross-sectional area ratio of the transparent thermal conductive filler to the transparent adhesive is about 13:7, which is the ratio of the cross-sectional area of the transparent thermal conductive filler to the transparent adhesive after the adhesive is coated and formed into a film.
[0108] The preparation method of the transparent thermally conductive adhesive comprises the following steps:
[0109] S1, mixing a nano thermally conductive filler, a surface modification agent, and 45 parts of ethyl acetate and soaking them for 24 hours, and then dispersing them in a ball mill at 2000 rpm for 20 minutes to obtain a nano thermally conductive filler slurry;
[0110] S2. Add a transparent thermally conductive filler to 75 parts of ethyl acetate and soak for 20 minutes, then add a transparent adhesive, use a high-speed disperser to stir at 1000 rpm for 30 minutes, then add the nano thermally conductive filler slurry obtained in step S1 and use the remaining 30 parts of ethyl acetate to rinse the dispersed thermally conductive filler to ensure that the filler in S1 is completely added, and use a high-speed disperser to continue dispersing for 30 minutes at 1000 rpm to obtain a transparent thermally conductive adhesive.
[0111] Comparative Example 1
[0112] A transparent thermally conductive adhesive, the raw material ratio of which is:
[0113] In parts by weight, the transparent adhesive, the transparent thermal conductive filler, the nano thermal conductive filler, the surface modification additive, and the ethyl acetate are 100 parts, 55 parts, 15 parts, 0.3 parts, and 150 parts, respectively.
[0114] The preparation method of the transparent adhesive comprises the following steps:
[0115] 1) Preparation of transparent acrylic adhesive:
[0116] By weight, 20 parts of o-phenylphenoxyethyl acrylate, 16 parts of 4-biphenylmethanol acrylate, 15 parts of hydroxyethyl acrylate as a soft monomer, 30 parts of cyclohexyl acrylate, 15 parts of isobornyl acrylate as a hard monomer, 3 parts of hydroxyethyl acrylate as a functional monomer, 1 part of acrylic acid, 0.6 parts of azobisisobutyronitrile initiator, 80 parts of ethyl acetate, and 40 parts of butanone are mixed, and reacted at 66° C. for 3 hours, 75° C. for 2 hours, and 78° C. for 2 hours under nitrogen flow to obtain a transparent acrylic adhesive; the refractive index is 1.54, and the transmittance is 95%;
[0117] 2) Add 2 parts by weight of curing agent isocyanate L75 to the transparent acrylic adhesive and stir evenly to obtain a transparent adhesive.
[0118] The transparent thermal conductive filler is spherical quartz powder with a D50 of 30μm and a D100 of 46μm, the nano thermal conductive filler is spherical nano alumina powder with a D50 of 28nm and a D100 of 265nm, and the surface dispersant is the acrylate hyperdispersant DISPERBYK-2022 purchased from BYK, Germany. The cross-sectional area ratio of the transparent thermal conductive filler to the transparent adhesive is about 2:3, which is the ratio of the cross-sectional area of the transparent thermal conductive filler to the transparent adhesive after the adhesive is coated and formed into a film.
[0119] The preparation method of the transparent thermally conductive adhesive comprises the following steps:
[0120] S1, mixing a nano thermally conductive filler, a surface modification agent, and 45 parts of ethyl acetate and soaking them for 24 hours, and then dispersing them in a ball mill at 2000 rpm for 20 minutes to obtain a nano thermally conductive filler slurry;
[0121] S2. Add a transparent thermally conductive filler to 45 parts of ethyl acetate and soak for 20 minutes, then add a transparent adhesive, use a high-speed disperser to stir at 1000 rpm for 30 minutes, then add the nano thermally conductive filler slurry obtained in step S1 and use the remaining 60 parts of ethyl acetate to rinse the dispersed thermally conductive filler to ensure that the filler in S1 is completely added, and use a high-speed disperser to continue dispersing for 30 minutes at 1000 rpm to obtain a transparent thermally conductive adhesive.
[0122] Comparative Example 2
[0123] A transparent thermally conductive adhesive, the raw material ratio of which is:
[0124] In parts by weight, the transparent adhesive, the transparent thermal conductive filler, the nano thermal conductive filler, the surface modification additive, and the ethyl acetate are 100 parts, 118 parts, 25 parts, 0.5 parts, and 150 parts, respectively.
[0125] The preparation method of the transparent adhesive comprises the following steps:
[0126] 1) Preparation of transparent acrylic adhesive:
[0127] By weight, 20 parts of o-phenylphenoxyethyl acrylate, 16 parts of 4-biphenylmethanol acrylate, 15 parts of hydroxyethyl acrylate as a soft monomer, 30 parts of cyclohexyl acrylate, 15 parts of isobornyl acrylate as a hard monomer, 3 parts of hydroxyethyl acrylate as a functional monomer, 1 part of acrylic acid, 0.6 parts of azobisisobutyronitrile initiator, 80 parts of ethyl acetate, and 40 parts of butanone are mixed, and reacted at 66° C. for 3 hours, 75° C. for 2 hours, and 78° C. for 2 hours under nitrogen flow to obtain a transparent acrylic adhesive; the refractive index is 1.54, and the transmittance is 95%;
[0128] 2) Add 2 parts by weight of curing agent isocyanate L75 to the transparent acrylic adhesive and stir evenly to obtain a transparent adhesive.
[0129] The transparent thermal conductive filler is spherical quartz powder with a D50 of 30μm and a D100 of 46μm, the nano thermal conductive filler is spherical nano alumina powder with a D50 of 28nm and a D100 of 265nm, and the surface dispersant is the acrylate hyperdispersant DISPERBYK-2022 purchased from BYK, Germany. The cross-sectional area ratio of the transparent thermal conductive filler to the transparent adhesive is about 2:3, which is the ratio of the cross-sectional area of the transparent thermal conductive filler to the transparent adhesive after the adhesive is coated and formed into a film.
[0130] The preparation method of the transparent thermally conductive adhesive comprises the following steps:
[0131] S1, mixing a nano thermally conductive filler, a surface modification agent, and 75 parts of ethyl acetate and soaking them for 24 hours, and then dispersing them in a ball mill at 2000 rpm for 20 minutes to obtain a nano thermally conductive filler slurry;
[0132] S2. Add a transparent thermally conductive filler into 60 parts of ethyl acetate and soak for 20 minutes, then add a transparent adhesive, use a high-speed disperser to stir at 1000 rpm for 30 minutes, then add the nano thermally conductive filler slurry obtained in step S1 and use the remaining 15 parts of ethyl acetate to rinse the dispersed thermally conductive filler to ensure that the filler in S1 is completely added, and use a high-speed disperser to continue dispersing for 30 minutes at 1000 rpm to obtain a transparent thermally conductive adhesive.
[0133] Comparative Example 3
[0134] A transparent thermally conductive adhesive, the raw material ratio of which is:
[0135] In parts by weight, the transparent adhesive, the transparent thermal conductive filler, the nano thermal conductive filler, the surface modification additive, and the ethyl acetate are 100 parts, 180 parts, 15 parts, 0.3 parts, and 150 parts, respectively.
[0136] The preparation method of the transparent adhesive comprises the following steps:
[0137] 1) Preparation of transparent acrylic adhesive:
[0138] By weight, 20 parts of o-phenylphenoxyethyl acrylate, 16 parts of 4-biphenylmethanol acrylate, 15 parts of hydroxyethyl acrylate as a soft monomer, 30 parts of cyclohexyl acrylate, 15 parts of isobornyl acrylate as a hard monomer, 3 parts of hydroxyethyl acrylate as a functional monomer, 1 part of acrylic acid, 0.6 parts of azobisisobutyronitrile initiator, 80 parts of ethyl acetate, and 40 parts of butanone are mixed, and reacted at 66° C. for 3 hours, 75° C. for 2 hours, and 78° C. for 2 hours under nitrogen flow to obtain a transparent acrylic adhesive; the refractive index is 1.54, and the transmittance is 95%;
[0139] 2) Add 2 parts by weight of curing agent isocyanate L75 to the transparent acrylic adhesive and stir evenly to obtain a transparent adhesive.
[0140] The transparent thermal conductive filler is a spherical quartz powder with a D50 of 30μm and a D100 of 46μm, the nano thermal conductive filler is a spherical nano alumina powder with a D50 of 28nm and a D100 of 265nm, and the surface dispersant is an acrylate hyperdispersant DISPERBYK-2022 purchased from BYK, Germany. The cross-sectional area ratio of the transparent thermal conductive filler to the transparent adhesive is about 7:3, and the cross-sectional area ratio is the ratio of the cross-sectional area of the transparent thermal conductive filler to the transparent adhesive after the adhesive is coated and formed into a film.
[0141] The preparation method of the transparent thermally conductive adhesive comprises the following steps:
[0142] S1, mixing a nano thermally conductive filler, a surface modification agent, and 45 parts of ethyl acetate and soaking them for 24 hours, and then dispersing them in a ball mill at 2000 rpm for 20 minutes to obtain a nano thermally conductive filler slurry;
[0143] S2. Add a transparent thermally conductive filler into 90 parts of ethyl acetate and soak for 20 minutes, then add a transparent adhesive, use a high-speed disperser to stir at 1000 rpm for 30 minutes, then add the nano thermally conductive filler slurry obtained in step S1 and use the remaining 15 parts of ethyl acetate to rinse the dispersed thermally conductive filler to ensure that the filler in S1 is completely added, and use a high-speed disperser to continue dispersing for 30 minutes at 1000 rpm to obtain a transparent thermally conductive adhesive.
[0144] Test Case
[0145] The thermally conductive adhesives prepared in Examples 1-5 and Comparative Examples 1-3 were prepared into adhesive tape products according to the following method:
[0146] The transparent thermally conductive adhesive was coated on the release material (PET release film) using a scraper, and baked in an oven at 60-130 degrees for 10 minutes to dry the solvent to form an adhesive layer with a thickness of 50 μm, thereby obtaining a transparent thermally conductive tape for subsequent testing.
[0147] Light transmittance, tested according to the test standard GB / T 2410-2008;
[0148] Haze, tested according to the test standard GB / T 2410-2008;
[0149] Thermal conductivity, tested according to test standard ASTM D5470-06;
[0150] Volume resistivity, tested according to the test standard GB / T 1410-2006;
[0151] The test results are shown in Table 1 below:
[0152] Table 1
[0153]
[0154] From the test results in Table 1, it can be seen that the adhesive tapes prepared in Examples 1-5 have high thermal conductivity, high light transmittance, low haze, and excellent comprehensive performance;
[0155] In comparative example 1, the proportion of thermal conductive particles is low, and the overall transmittance and haze are improved, but the thermal conductivity is low. In comparative example 2, the amount of nano thermal conductive particles is increased, but the difference in thermal conductivity is not obvious and it will affect the transmittance and haze. In comparative example 3, a higher amount of transparent thermal conductive particles is added, which can improve the thermal conductivity but leads to a significant decrease in transmittance and haze performance.
[0156] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A transparent thermally conductive adhesive, characterized in that: The invention comprises the following raw material components in parts by weight: 100 parts of transparent adhesive, 75-150 parts of transparent thermal conductive filler, 1-20 parts of nano thermal conductive filler, 1-3 parts of surface modification auxiliary agent and 150-300 parts of first solvent.
2. The transparent thermally conductive adhesive according to claim 1, characterized in that: The transparent adhesive is any one of transparent acrylic, transparent polyurethane, transparent epoxy, and transparent silicone adhesive, and the refractive index of the transparent adhesive is 1.5-1.
6.
3. The transparent thermally conductive adhesive according to claim 2, characterized in that: The transparent adhesive is a transparent acrylic adhesive added with a curing agent, and the raw materials for preparing the transparent acrylic adhesive include, by weight: 15-40 parts of a high refractive index acrylic monomer, 2-20 parts of a hard monomer, 40-70 parts of a soft monomer, 1-5 parts of a functional monomer, 0.1-1 parts of an initiator, and 60-150 parts of a second solvent; The amount of curing agent added is 1-4 parts.
4. The transparent thermally conductive adhesive according to claim 3, characterized in that: The preparation method of the transparent adhesive comprises the following steps: 1) Preparation of transparent acrylic adhesive: By weight, 15-40 parts of a high refractive index acrylic monomer, 2-20 parts of a hard monomer, 40-70 parts of a soft monomer, 1-5 parts of a functional monomer, 0.1-1 parts of an initiator and 60-150 parts of a second solvent are mixed, and reacted under nitrogen flow to obtain a transparent acrylic adhesive; 2) Add 1-4 parts by weight of a curing agent to the transparent acrylic adhesive and stir evenly to obtain the transparent adhesive.
5. The transparent thermally conductive adhesive according to claim 1, characterized in that: The high refractive index acrylic monomer is at least one of o-phenylphenoxyethyl acrylate, 4-biphenylmethanol acrylate, benzyl methacrylate, 1-naphthyl methacrylate, trimethylolpropane tris(3-mercaptopropionate) and the like. The soft monomer is at least one of hydroxyethyl acrylate and cyclohexyl acrylate; The hard monomer is isobornyl acrylate; The functional monomer is at least one of hydroxyethyl acrylate and acrylic acid; The curing agent is one or more of an epoxy curing agent, an isocyanate curing agent, and an aziridine curing agent; The first solvent and the second solvent are one or more of ethyl acetate, butanone, acetone, toluene, xylene, and butyl acetate.
6. The transparent thermally conductive adhesive according to claim 1, characterized in that: The transparent thermal conductive filler is transparent quartz powder with a thermal conductivity of 7-10W / m·K and a refractive index of 1.54-1.55; The particle size of the transparent quartz powder and the thickness of the adhesive layer formed after the transparent thermal conductive adhesive is cured satisfy the following relationship: D50 particle size>1 / 2 adhesive thickness, D90 particle size<3 / 4 adhesive thickness, and D100 particle size<adhesive thickness.
7. The transparent thermally conductive adhesive according to claim 1, characterized in that: The nano thermal conductive filler is one or more of nano aluminum oxide, nano boron nitride, nano titanium oxide, nano zinc oxide, nano aluminum nitride, nano diamond, etc., and the maximum particle size of the nano filler is less than 380nm.
8. The transparent thermally conductive adhesive according to claim 1, characterized in that: The surface modification aid is one or more of a coupling agent, a surfactant, and a dispersant.
9. A method for preparing a transparent thermally conductive adhesive as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: S1, dividing the first solvent into two parts, mixing the nano thermal conductive filler, the surface modification agent, and the first part of the first solvent and soaking them for 12-48 hours, and then dispersing them for 10-60 minutes to obtain a nano thermal conductive filler slurry; S2, adding a transparent thermally conductive filler into the second part of the first solvent and soaking for 10-40 minutes, then adding a transparent adhesive, stirring for 10-30 minutes, and then adding the nano thermally conductive filler slurry obtained in step S1, and continuing to disperse for 10-60 minutes to obtain the transparent thermally conductive adhesive.
10. A transparent thermally conductive tape, characterized in that: The transparent thermally conductive adhesive tape is prepared by the following method: the transparent thermally conductive adhesive as claimed in claim 9 is evenly coated on the surface of the release material, dried, and aged at 35-70° C. for 1-5 days to obtain the transparent thermally conductive adhesive tape.